Antimony (V) Oxide Adsorbed on a Silica-Zirconia Mixed Oxide Obtained by the Sol-Gel Processing Method: Preparation and Acid Properties - Zaitseva Galina; Gushikem Yoshitaka (Journal of the Brazilian Chemical Society, 2002)
The preparation, degree of dispersion, thermal stability and Lewis and Brphinsted acidity of antimony (V) oxide adsorbed on SiO2/ZrO2 mixed oxide, previously prepared by the sol-gel processing method, are described herein. The samples SiO2/ZrO2/Sb2O5, with compositions (in wt %): (a) Zr= 8.1 and Sb= 6.3; (b) Zr= 14.9 and Sb= 11.4, were prepared. Scanning electron microscopy images connected to a X-ray energy dispersive spectrometer showed that both metals, Zr and Sb, were highly dispersed in the matrices. The X-ray diffraction patterns of SiO2/ZrO2/Sb2O5 heated at different temperatures showed that, up to 1023 K, the matrix was amorphous. At 1273 K a crystalline phase of ZrO2 (baddeleyite) was observed and raising the temperature to 1573 K, crystalline phases of SiO2 (cristobalite) and presumably of ZrO2/Sb2O5 were observed. Using pyridine as a molecular probe, Brphinsted acid sites on the SiO2/ZrO2/Sb2O5 matrix, heat treated up to 523 K, were shown to be very stable.